Vegetarian diets and risk of hospitalisation or death with diabetes in British adults: Results from the EPIC-Oxford study - Papier, K; Appleby, P; Fensom, G; Knuppel, A; Perez-Cornago, A; Schmidt, J; Tong, T; Key, T (Springer Nature, 2019)
Background The global prevalence of diabetes is high and rapidly increasing. Some previous studies have found that vegetarians might have a lower risk of diabetes than non-vegetarians. Objective We examined the association between vegetarianism and risk of hospitalisation or death with diabetes in a large, prospective cohort study of British adults. Methods The analysed cohort included participants from the European Prospective Investigation into Cancer and Nutrition (EPIC)-Oxford study who were diabetes free at recruitment (1993–2001), with available dietary intake data at baseline, and linked hospital admissions and death data for diabetes over follow-up (n = 45,314). Participants were categorised as regular meat eaters (≥50 g per day: n = 15,181); low meat eaters (<50 g of meat per day: n = 7615); fish eaters (ate no meat but consumed fish: n = 7092); and vegetarians (ate no meat or fish, including vegans: n = 15,426). We used multivariable Cox proportional hazards models to assess associations between diet group and risk of diabetes. Results Over a mean of 17.6 years of follow-up, 1224 incident cases of diabetes were recorded. Compared with regular meat eaters, the low meat eaters, fish eaters, and vegetarians were less likely to develop diabetes (hazard ratio (HR) = 0.63, 95% confidence interval (CI) 0.54–0.75; HR = 0.47, 95% CI 0.38–0.59; and HR = 0.63, 95% CI 0.54–0.74, respectively). These associations were substantially attenuated after adjusting for body mass index (BMI) (low meat eaters: HR = 0.78, 95% CI 0.66–0.92; fish eaters: HR = 0.64, 95% CI 0.51–0.80; and vegetarians: HR = 0.89, 95% CI 0.76–1.05). Conclusions Low meat and non-meat eaters had a lower risk of diabetes, in part because of a lower BMI.